The Western Time of Ancient History : Historiographical Encounters with the Greek and Roman Pasts. - Lianeri, Alexandra (Cambridge University Press, 2011)
Distinguished European scholars discuss the conceptual and temporal frames through which modern Western historiography has linked itself to classical antiquity.